Repeat radiofrequency catheter ablation of atrial tachycardias in patients with congenital heart disease. (18th April 2022) - Klehs, Sophia; Schneider, Heike E.; Backhoff, David; Müller, Matthias J.; Paul, Thomas; Krause, Ulrich
Abstract: Introduction: Atrial tachycardias (AT) in patients with congenital heart disease (CHD) are significantly contributing to morbidity and mortality. Aim of this study was to evaluate the long‐term course of CHD patients requiring repeat ablation procedures (RAP) of AT. Patients and Methods: All 144 patients with CHD who had undergone ablation of AT at our center between January 2003 and October 2018 were enrolled. Patients were classified according to the complexity of CHD: complex CHD (cCHD), moderate CHD (mCHD), and simple CHD (sCHD). Results: A total of 101 RAP were performed in 64 patients. One RAP was performed in n  = 40, two in n  = 13, three in n  = 10, and five in n  = 1. Acute success rate was 82% (83/101) and was not associated with the complexity of CHD ( p  = 1.0). Number of procedures was lower in patients with sCHD than in patients with mCHD and cCHD (sCHD 1.3 ± 0.6, mCHD 1.8 ± 1.0, and cCHD 1.8 ± 1.1, p  = .04). RAP were most frequent in patients after Fontan palliation or Atrial switch procedure (2.0 ± 1.1 [ n  = 41] vs. 1.6 ± 0.9 all others, p  = .016) and in patients with multiple unstable AT's (2.5 ± 1.1 [ n  = 11] vs. 1.7 ± 1.0, p  = .008). Major complications occurred in 4/101 procedures. Complete follow‐up was available in 125 patients. Since last RAP 73% of the patients were in sinus/atrial rhythm and 34/125 patients (27%) with AT recurrence did not require re‐ablation with mean follow‐up of 52 ± 40 months. Conclusions: Recurrences after ablation of AT in CHD patients were frequent. After RAP promising long‐term results could be achieved. Data encourage repetitive ablation procedures in this patient population.